Prediksi Cakupan Area untuk Jaringan Wireless Indoor Kampus berdasarkan Penempatan Access Point - Fransiska Sisilia Mukti; Allin Junikhah (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2019)
The placement of a transmitter in a wireless network (access point) is one of the essential things which must be considered by the network designer. The right placement will give the maximum signal spread, especially for the closed environment, because of the effect of the indoor propagation, which affects the signal strength decrease significantly. Every AP’s placement point will have different signal spread pattern, including the coverage area. The AP placement process carried out so far still uses conventional methods, namely trial-error, which requires a long time to analyze its performance. A coverage prediction system modeling is built to determine the spread of signals generated by an AP. This modeling is done using a statistical approach in 2D. The modeling did a visualization that is run through software and gives the result of mapping the coverage area of an AP. The test results show that the percentage of area coverage generated based on the AP placement used is currently 72.5%. There are still areas that are not covered by the AP, especially for the NLOS propagation path because of the obstruction around the AP. The maximum distance between the AP and the user so that it is within the coverage area is 13.21m